Early Elective Surgery After Colon Cancer Diagnosis has Higher Risk of Readmission and Death. Issue 2 (February 2021) - Gleason, Frank; Chu, Daniel I.; Kennedy, Gregory D.; Kenzik, Kelly M.
Abstract : Objective: We hypothesized colon resection within 30 days of diagnosis of cancer would have higher rates of readmission and cancer specific mortality, unless there was demonstrated evidence of preoperative workup. Summary Background Data: Few studies have examined if negative consequences exist with expedited elective surgery after diagnosis of colon cancer. Surgery in a shorter time frame may result in a lack of appropriate preoperative care. Methods: Retrospective analysis of 25, 407 patients in the Surveillance Epidemiology and End Results registry who underwent elective surgical resection for colon cancer from 2010 to 2015. Cohort stratified by age (66–75 vs >75 years). Primary outcomes of interest were 30-day readmission and 5-year colon cancer specific mortality. Relationships between timing of surgery and outcomes were assessed. Results: On unadjusted analysis, surgery before 20 days of diagnosis was associated with higher risk of 30-day readmission and colon cancer specific mortality in both age groups. Among those age 66 to 75 years old, adjusting for patient factors and preoperative workup eliminated the risk of 30-day readmission (risk ratio 1.5–0.9 for 0–10 days, risk ratio 1.3–0.9 for 11–20 days). However, the risk for colon cancer specific mortality, although reduced, persisted (hazard ratio 2.2–1.3 for 0–10 days, hazard ratio 2.0–1.2 for 11–20 days). In the cohort older than 75 years, adjusting for patient level factors and preoperative workup eliminated risk of surgery 20 days postop or sooner. Conclusions: The risk associated with short time to surgery (within 30 days) may be mitigated if full oncologic workups are provided. Abstract : Supplemental Digital Content is available in the text